The Evolution and Structural Organization of the Organs of Vertebrate Immune System - Sotnikova, Elena D. (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This study aimed to define the main ways of evolution of the organs of the immune system in vertebrate animals that include the segregation, i.e., the separation of the organs of immune system from the hematopoietic system, on the basis of which they were formed; differentiation, i.e., the division of initially integrated lymphoid structures into diffuse clumps, lymphoid nodules, and the germinal centers; transformation, i.e., the transfiguration of rudimentary organs into organs of the immune system; and polymerization, i.e., the increase in the number of peripheral organs of immunogenesis in phylogenesis. Materials and Methods: This is a comparative analysis of the morphology of the organs of immune system in those orders of birds and mammals which have passed in their development in different periods of time in terms of the fossil record. Statistical processing of the obtained digital data was conducted by individually tailored programs. Results and Conclusions: Conducted research demonstrates the historical trend of immune system in terms of morphological progress, which is manifested in the alternation of relatively fast flowing aromorphoses with longer periods of idioadaptations.